Earn your MBA on the toilet : unleash unlimited power and wealth from your bathroom - Kasper Hauser Comedy Group (Berkeley : Ten Speed Press, 2013)
"A faux "guidebook" for business school graduates, intended to parody MBA programs and American business culture in general"--
Keywords: Master of business administration degree -- Humor; HUMOR / Topic / Business & Professional; HUMOR / Form / Parodies